P5_10 Can Vacuum’s Save The World? - Cox, Tom; Penn Fernandez, Keaton; Mead, Lara; Seagrave, Joshua (Physics Special Topics, 2020)
Global warming has been a major problem for humanity since the industrial revolution, carbon dioxide emissions are now sky high due to increased energy demands every year. Large efforts are now taking place to slow down our CO2 emissions and postpone global warming. In this paper we show how Climeworks vacuum cleaners operate and calculate that a power supply of 1.74×10^20 J/yr is required, to clean the global annual CO2 emissions. This power supply is equivalent to 59.88 and 11.56 times larger than the USA’s nuclear and total power output respectively in 2018.